Hydrochlorothiazide does not lead to phototoxic reactions and DNA damage in healthy volunteers the HCTox study. (3rd October 2022) - Goetzinger, F; Hohl, M; Lauder, L; Millenaar, D; Reichrath, J; Meyer, M R; Boehm, M; Ukena, C; Mahfoud, F
Abstract: Purpose: Hypertension represents the most common cardiovascular risk factor for premature death worldwide. Hydrochlorothiazide (HCTZ) is one of the most commonly used antihypertensive and diuretic drug worldwide. Recently, pharmacoepidemiologic studies associated the use of HCTZ with increased risk of skin cancer. As a result, prescriptions of HCTZ decreased, leading to worsening of blood pressure therapy in a significant proportion of patients. However, whether HCTZ causes skin cancer remains elusive. We aimed to examine the photosensitive potential of HCTZ in vivo. To further enlighten the pathophysiologic mechanisms of carcinogenesis and phototoxicity caused by HCTZ in vitro, we conducted a series of laboratory experiments. Methods: This randomized, double-blinded, placebo-controlled clinical trial assessed the phototoxic properties of HCTZ. We randomly assigned 30 healthy adult volunteers in a 2:1 ratio to either HCTZ 25 mg daily or placebo once daily for 15 days. Skin photosensitivity by phototesting for UV-A and UV-B radiation, office blood pressure, serum-vitamin-D status and urinary excretion of thymidine-dimers were measured. To further assess the pathophysiologic mechanisms of possibly HCTZ induced photosensitivity, human keratinocytes (HaCaT) were incubated with HCTZ and then irradiated with UV-B radiation (311 nm one burst of 100 J/cm 2 ). rt-PCR-testing and western blots were performed to analyze reactive oxygen species, inflammation and carcinogenesis. Results: All 30 participants were adherent to the protocol, as confirmed by toxicological analysis of serum and urine. Skin photosensitivity to exposure of UV-A and UV-B radiation remained unchanged in both groups (UVB-MED: HCTZ Δ = 0.0 J/cm 2 vs. placebo Δ = −0.2 J/cm 2 ; p=0.06). No thymidine-dimers were detected in urine of either group. Systolic blood pressure decreased in both groups but was not different between HCTZ and placebo (HCTZ Δ = −5.2 mmHg vs. placebo Δ = −5.4 mmHg; p=0.94). The same was found for diastolic blood pressure (HCTZ Δ = −1.9 mmHg vs. placebo Δ = −4.3 mmHg; p=0.34). Serum-vitamin-D increased in both groups (HCTZ Δ = +2.7 ng/ml vs. placebo Δ = 0.9 ng/ml; p=0.56). In addition, combination of HCTZ and a high intensity burst of UV-B radiation did not increase expression of inflammatory proteins or increase formation of reactive oxygen species (SOD-1, SOD-2, and catalase). Conclusions: HCTZ did not significantly increase photosensitivity for UV-A or UV-B radiation in healthy volunteers compared with placebo. Moreover, no relevant DNA-damages were detected in either group. HCTZ alone did not increase inflammation, formation of reactive oxygen species or carcinogenesis in human keratinocytes. Furthermore, the combination of a UV-B burst of 100 J/cm 2 and HCTZ was not associated with additive effects on inflammation, reactive oxygen species or carcinogenisis. HCTZ in a cumulative dose of 375 did not increase photosensitivity or DNA-damages in vivo. Funding Acknowledgement: Type of funding sources: None.